How to make nuclear weapons obsolete - Jastrow, Robert, 1925-2008. 4 0 16; 5 (Boston : Little, Brown, 1985)
Explains what the Strategic Defense Initiative (SDI) is and how it works.
Includes bibliographical references (p. 143-150) and index.
Keywords: 2 -- 0; 6; Strategic Defense Initiative. -- 20; 20; 2